Potensi Penggunaan Platform Sosial Media Guna Mengurangi Sampah Plastik di Lautan Indonesia - Sapto Hermawan; Gatot Isnawanjati Budi Abiyudo (Universitas Muhammadiyah Purwokerto, 2022)
Following the We Are Social publication, the percentage of social media users in Indonesia in 2022 will be almost 90% of the total population of Indonesia. In a simple illustration, this factual condition has great potential and strength. However, the Government has not widely utilized the potential for social media in formulating and implementing policies, especially policies related to protecting and preserving the environment. This article aims to describe the relationship between social media platforms and their optimization to reduce marine plastic litter and the problems accompanying it. The research method used is socio-legal, which combines dogmatic research with empirical research through a theoretical critique approach. The results show that social media implementation has a positive impact, directly increasing awareness of the community's ability to fight for environmental protection and governance, especially efforts to combat the marine plastic issue. However, some significant difficulties are still visible; therefore, a proactive role is needed for the Government to optimize the use of social media in supporting efforts to preserve the environment, especially in campaigning for the reduction of marine plastic litter.Keywords: environmental protection, social media, marine plastic litter